TUNCELİ İLİ EKONOMİK FAALİYETLERİNİN KÜLTÜR COĞRAFYASI AÇISINDAN İNCELENMESİ - OĞAN, SONGÜL (Fırat Üniveristesi, 2016)
Coğrafya, en basit tanımıyla insan ve mekân ilişkilerini inceleyen bir bilim dalıdır. Kültür insanın doğa karşısında doğayla birlikte yaşamını sürdürebilmesi için ürettiği her şeydir. Kültürlerin ve toplumların mekansal farklılıkları kültür coğrafyası tarafından incelenir. Tunceli İli Doğu Anadolu Bölgesi'nin Yukarı Fırat Bölümünde yer almaktadır. Doğuda Bingöl ve Elazığ, batıda ve kuzeyde Erzincan, güneyde ise Elazığ iliyle komşudur. Tunceli, 7. 774 km2 yüzölçümü ile Türkiye topraklarının % 1'ini kaplamaktadır. Tunceli İli, Fırat nehrinin iki ana kolu olan Murat ile Karasu nehirleri arasında, etrafını tabii bir duvar gibi çevreleyen Munzur ve Mercan dağlık kütleleri yamaçlarında kurulmuştur. Tunceli ili arazisinin, %70'ini dağlar, %25'ini platolar ve % 5'ini ova alanları oluşturur. Tunceli ilinde Karasal iklim hüküm sürmektedir. Yıllık toplam yağış miktarı 550-1080 mm arasında değişmektedir. Doğal koşulların fazlası ile etkilediği bir yaşam sahası ve buna bağlı gelişen ekonomik yapı daha çok hayvancılık ve çok az tarım faaliyetleri üzerine şekillenmiştir. Sanayi ve ticaret yok denecek kadar az gelişmiştir. Şehirleşme, göç, teknolojik yenilikler vb etmenler ile beraber geleneksel üretim araçları ve yaşam uğraşları terk edilmiş, ya yok olmuş ya da yok olmaya yüz tutmuştur. Çalışma sahasında geleneksel halk kültürünün etkisi ile şekillenen 40 meslek tespit edilmiştir. Anahtar Kelime: Kültür Coğrafyası, Tunceli, Munzur Dağları, Tunceli Sarmısağı (Allium Tuncelianum), Göç.

Geography, in the simplest term is a science that studies the relationship between people and places. Culture encompasses everything that human being produced in order to survive with nature. Spatial differences of cultures and communities are examined by the cultural geography. Tunceli Province is located in the Upper Euphrates of Eastern Anatolia Region. It is bordered by Bingöl and Elaziğ in the east, Erzincan in the North and west, Elazığ in the south. Tunceli covers 1% of the Turkey's territory with 7,774 km2 area. Tunceli province was established between Karasu and Murat rivers which are two main tributaries of the Euphrates, in the slope of Munzur and Mercan mountainous mass which surround it as a wall, and its surface area comprise 70% of mountains, 25% of plateaus and 5% of lowland areas. Continental climate is dominant in the Tunceli province. Its total annual rainfall varies between the range of 550-1080 mm. Economic structure based on living area affected predominantly by natural conditions is shaped over intensive stock farming and less agricultural activities. Commerce and industry sector is underdeveloped, almost nonexistent. Traditional manufacturing tools, professions and life pursuits emerged by the means of environmental conditions and cultural consciousness have been either abandoned or tend to disappear or even disappeared by virtue of urbanization, migration, technological innovation and etc. The study area has been detected in 40 career shaped by the influence of traditional folk culture. Keywords: Cultural Geography, Tunceli, Munzur Mountains, Tunceli Garlic (Allium Tuncelianum), Migration
Investigation of economic activities of Tunceli province from the point of cultural geography
Keywords: Coğrafya